Fingolimod‐improved axonal and myelin integrity of white matter tracts associated with multiple sclerosis‐related functional impairments. (5th January 2018) - Gurevich, Michael; Waknin, Roy; Stone, Evan; Achiron, Anat
Summary: Aims: Fingolimod hydrochloride is an effective immunomodulatory drug in improving relapsing‐remitting multiple sclerosis (RRMS). However, data on the neuroradiologic effects on white matter (WM) have not been demonstrated. In this study, we aimed elucidating the impact of 1‐year fingolimod treatment on WM integrity in patients with RRMS. Methods: Diffusion tensor imaging (DTI) was applied to assess axonal and myelin integrity in specific WM tracts of patients with RRMS prior to and 1 year postfingolimod treatment (n = 30). The fractional anisotropy (FA), radial diffusivity (RD), axial diffusivity, and mean diffusivity were analyzed using tract‐based spatial statistics on specific regions of interest associated with impaired Expanded Disability Status Scale functional scores before treatment. Results: In patients with impaired pyramidal function at baseline (average score 2.3 ± 0.2, n = 25), fingolimod induced a significant increase in FA ( P  = 0.002) and decrease in RD ( P  = 0.03) in the corticospinal tract. In patients with impaired cerebellar function at baseline (average score 2.0 ± 0.1, n = 19), significant increases in FA and decreases in RD were observed in the superior ( P  = 0.02, P  = 0.01, respectively) and inferior ( P  = 0.03, P  = 0.05, respectively) cerebellar peduncles. Conclusion: The observed results suggest increased microstructural integrity and decreased demyelination of damaged WM tracts and support the possible direct mechanism of fingolimod action.